KINERJA KEUANGAN BERKELANJUTAN PERUSAHAAN ASURANSI SYARIAH YANG TERINTEGRASI DENGAN ASPEK ESG DAN MAQASHID SYARIAH - Wijaya, Sangkut (Syar'Insurance: Jurnal Asuransi Syariah, 2023)
This article is aimed to examine the possibility of establishing an ESG and Maqashid Syariah index or rating for sharia insurance companies in an integrated manner. The sharia insurance company’s financial report and sustainability report will be more powerful to portray the comprehensive performance of the company if completed with Maqashid Syariah and they integrate into a standardized index/rating. Through a literature analysis approach, this research results that the formation of an ESG and Maqashid Syariah index or rating for sharia insurance companies in an integrated manner needs to be carried out with adjustments that can be discussed previously, for example, in an FGD involving various stakeholders in the sharia insurance industry. Thus, in the future there will be a standard measure of sustainable financial performance that can be compared (comparable) in the sharia insurance industry in Indonesia which describes financial performance which is reliable, sustainable, and mashlahah.